An Analysis of Soil Salinity as an Ecological Issue (International Journal of Innovative Research in Computer Science & Technology, 2022)
Salinity is one among most serious  ecological issues affecting farmed vegetation yield  although most seeds are prone to saline induced by  excessive salt content in soil, & amount of l& affected by  it is increasing by day.. Average yields for all main crops  are a fraction of record yields, ranging between 20% & 50%; se losses are majorly owing to dearth & excessive  soil salinity, climatic circumstances that are expected to  worsen in many locations as a result of global climate  change. number of variations & mitigation techniques are  m&atory for deal with such consequences. In order to  generate better breeds, salinity stress can be reduced by  effective resource management & crop/livestock growth.  However, because such treatments are time-consuming & expensive, simple & low-cost biological options for  salinity stress reduction that can be adopted rapidly are  needed.. Microorganisms with unique characteristics like salt tolerance, genetic diversity, synsis of suitable solutes,  & generation of vegetation growth boosting hormones,  bio-control capability, & contact with crop vegetations  may play a major role in this regard.
Keywords: Agricultural; Salinity; Salt; Soil; Water